2012
DOI: 10.3987/com-12-12502
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Nitro Group Substitution. Synthesis of Isomeric 4-Amino-5-nitro- and 5-Amino-4-nitroimidazoles

Abstract: On the basis of the reactions between 4,5-dinitroimidazole derivatives(1-methyl-4,5-dinitroimidazole, 1,2-dimethyl-4,5-dinitroimidazole and ethyl 2-(4,5-dinitroimidazol-1-yl)acetate) and cyclic amines (morpholine, piperidine or pyrrolidine) in mild conditions (THF or ethanolic solution), the order of nitro group substitution has been discovered for the first time. The influence of the solvent, steric effects and possibility of hydrogen bonds formation on the reaction direction has been discussed. Also, the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The Cambridge Structural Database (Groom & Allen, 2014) reveals only five structures of imidazole derivatives with a CH 2 COOCH 2 CH 3 substituent on nitrogen (Cai et al, 2014;Bahnous et al, 2013;Zaprutko et al, 2012). Imidazoles with benzoyl substituents are slightly more common with eight occurrences (Xue et al, 2014;Nagaraj et al, 2012;Samanta et al, 2013), while the structures of only six p-tolyl-substituted imidazoles are found (Bu et al, 1996;Fridman et al, 2006Fridman et al, , 2009.…”
Section: Database Surveymentioning
confidence: 99%
“…The Cambridge Structural Database (Groom & Allen, 2014) reveals only five structures of imidazole derivatives with a CH 2 COOCH 2 CH 3 substituent on nitrogen (Cai et al, 2014;Bahnous et al, 2013;Zaprutko et al, 2012). Imidazoles with benzoyl substituents are slightly more common with eight occurrences (Xue et al, 2014;Nagaraj et al, 2012;Samanta et al, 2013), while the structures of only six p-tolyl-substituted imidazoles are found (Bu et al, 1996;Fridman et al, 2006Fridman et al, , 2009.…”
Section: Database Surveymentioning
confidence: 99%